2016
DOI: 10.9778/cmajo.20150009
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding difficulties and supports and risk of postpartum depression in a cohort of womenwho have given birth in Calgary: a prospective cohort study

Abstract: Background:A link exists between breastfeeding difficulties and postpartum depression, and evidence shows that some breastfeeding promotion initiatives may increase maternal stress and contribute to risk of the condition. We conducted a prospective cohort study to determine whether breastfeeding difficulties affect the risk of postpartum depression and whether breastfeeding support modifies the relationship between breastfeeding difficulties and postpartum depression. Methods:Between June and October 2010, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 62 publications
3
54
3
Order By: Relevance
“…A previous study in Canada showed that a negative breastfeeding support experience was a significant effect modifier on the relationship between breastfeeding difficulties and postpartum depression [14]. The authors suggested that the quality of breastfeeding support was important not only to promote breastfeeding but also to insure maternal mental health through providing mothers with emotional and psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Canada showed that a negative breastfeeding support experience was a significant effect modifier on the relationship between breastfeeding difficulties and postpartum depression [14]. The authors suggested that the quality of breastfeeding support was important not only to promote breastfeeding but also to insure maternal mental health through providing mothers with emotional and psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…Though relatively infrequent it represents a substantial burden of disease . Lactating women are at particular risk, potentially disrupting the bond between mother and baby, and it may affect mental health …”
Section: Demographic and Clinical Profile Of Study Subjectsmentioning
confidence: 99%
“…2 Lactating women are at particular risk, potentially disrupting the bond between mother and baby, and it may affect mental health. 3 No consensus exists on the most appropriate antibiotic regime, nor the benefits of primary incision and drainage (I&D) versus ultrasound (US) guided aspiration. 4 Most centres favour broad-spectrum antibiotics and aspiration in uncomplicated BA as first-line treatment.…”
Section: Funding Information Aid Cancer Treamentmentioning
confidence: 99%
“…Quality breastfeeding promotion has the potential to reduce postpartum depression (Chaput et al 2016). Establishing meaningful contacts with families to encourage breastfeeding is recommended (PHE 2016b).…”
Section: Supporting Breastfeeding In Context -Child and Family Publicmentioning
confidence: 99%